"Those emblems of hell"? : European sailors and the maritime labour market, 1570-1870 - Royen, P. C. van; Lucassen, Jan; Bruijn, Jaap (Research in maritime history, 2017)
This volume collects a series of reports from maritime historians across Europe, aiming to provide a coherent historical trajectory of the lives of European sailors and their dealings with the maritime labour market.